Characterization of Coxsackievirus A6 Strains Isolated From Children With Hand, Foot, and Mouth Disease - Liu, Hongbo; Zhang, Ming; Feng, Changzeng; Cong, Shanri; Xu, Danhan; Sun, Hao; Yang, Zhaoqing; Ma, Shaohui (Frontiers in Cellular and Infection Microbiology, 2021)
Coxsackievirus A6 (CVA6) is a key pathogen causing hand, foot and mouth disease (HFMD). However, there are currently no specific antiviral drugs or vaccines for treating infections caused by CVA6. In this study, human rhabdomyosarcoma (RD), African green monkey kidney (Vero), and human embryonic lung diploid fibroblast (KMB17) cells were used to isolate CVA6 from 327 anal swab and fecal samples obtained during HFMD monitoring between 2009 and 2017. The VP1 genes of the isolates were sequenced and genotyped, and the biological characteristics of the representative CVA6 strains were analysed. A total of 37 CVA6 strains of the D3 gene subtypes were isolated from RD cells, all of which belonged to the epidemic strains in mainland China. Using the adaptive culture method, 10 KMB17 cell-adapted strains were obtained; however, no Vero cell-adapted strains were acquired. Among the KMB17 cell-adapted strains, only KYN-A1205 caused disease or partial death in suckling mice, and its virulence was stronger than its RD cell-adapted strain. The pathogenic KYN-A1205 strain caused strong tropism to the muscle tissue and led to pathological changes, including muscle necrosis and nuclear fragmentation in the forelimb and hindlimb. Sequence analysis demonstrated that the KYN-A1205 strain exhibited multiple amino acid mutations after KMB17 cell adaptation. Moreover, it showed strong pathogenicity, good immunogenicity and genetic stability, and could be used as an experimental CVA6 vaccine candidate.